Tellurites of Some s–f Elements: Synthesis, X-Ray Diffraction, and Electrophysical Properties - Rustembekov, K.T.; Dyusekeeva, A.T. (Springer, 2012)
A possibility of solid-phase synthesis of new cerium double tellurites with s-elements from the oxides of cerium(IV), tellurium(IV) and magnesium (calcium, strontium) carbonates was demonstrated. It was determined by the X-ray diffraction method that the magnesium-cerium tellurite crystallizes in a cubic system, while calcium-cerium and strontium-cerium tellurites crystallize in the tetragonal crystal system.The temperature dependence of the electrical resistance of these compounds in the range of 300-600 K was measured. The plots include sharp anomalous jumps due probably to the phase transitions of type II.
Keywords: Synthesis; X-Ray Diffraction; Electrophysical Properties